Peningkatan Mutu Pengabdian melalui In-Tray Training di “Rumah Pengabdian” UIN Sunan Gunung Djati Bandung - Aep Kusnawan; Sitta Resmiati Muslimah; Fathya Zulva Fadlilah Salma (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
Efforts to improve the quality of community service are essential. Apart from the fact that community service is part of the Tri Dharma of Higher Education, it is also one of the measures for Higher Education regarding its existence in the community. Efforts to improve the quality of community service are now being pursued by the Center for Community Service (PkM) UIN Sunan Gunung Djati Bandung, among others, through the "House of Service" pilot. In the "House of Service," the In Tray-Training of the servants is organized. The purpose of this discussion is to find out how the In-Tray Training activities are related to efforts to improve the quality of service. This discussion also uses the In-Tray Training method. The results show several improvements, among others: First, it offers an increase in the enthusiasm for service among the academic community of UIN Bandung. Second, the service house is a vehicle for meeting the service activist lecturers to hold in-tray training to exchange thoughts, ideas, methodologies, and service experiences and synergize various programs and steps of UIN SGD Bandung servants. To encourage servants in multiple faculties and study programs to synergize more, collaborate, complement each other, and give birth to innovation and form a distinction of different models and methods of service of UIN Bandung. Third, various community service activities carried out by the academic community of UIN SGD Bandung have also been successfully documented in an archived and publicized UIN Sunan Gunung Djati Bandung Community Service Profile book. Upaya peningkatan mutu pengabdian merupakan sesuatu yang penting. Selain karena Pengabdian kepada Masyarakat merupakan bagian dari Tri Dharma Perguruan Tinggi, ia juga menjadi salah satu ukuran bagi Perguruan Tinggi mengenai eksistensinya di tengah masyarakat. Upaya peningkatan mutu pengabdian itu, kini diupayakan oleh Pusat Pengabdian kepada Masyarakat (PkM) UIN Sunan Gunung Djati Bandung, antara lain melalui rintisan “Rumah Pengabdian”. Pada “Rumah Pengabdian” tersebut diselenggarakan In Tray-Training para pengabdi. Tujuan dari pembahasan ini, adalah untuk mengetahui bagaimana kegiatan In-Tray Training tersebut kaitannya dengan upaya peningkatan mutu pengabdian. Pembahasan ini juga menggunakan metode In-Tray Training. Hasilnya menunjukkan adanya beberapa peningkatan, antara lain: Pertama, Menampakkan peningkatan kegairahan mengabdi dikalangan para civitas akademika UIN Bandung. Kedua, keberadaan rumah pengabdian sebagai wahana bertemunya para dosen pegiat pengabdian melangsungkan in-tray training untuk saling bertukar pikiran, gagasan, metodologi, pengalaman pengabdian serta mensinergikan berbagai program dan gerak langkah para pengabdi UIN SGD Bandung. Sehingga mendorong para pengabdi di berbagai fakultas dan prodi lebih bersinergi, bisa berkolaborasi, saling mengisi dan melahirkan inovasi dan membentuk distingsi ragam model dan metode pengabdian UIN Bandung. Ketiga, Berbagai kegiatan pengabdian yang dilakukan oleh civitas akademika UIN SGD Bandung juga berhasil didokumentasikan menjadi buku Profile Pengabdi UIN Sunan Gunung Djati Bandung yang terarsipkan dan terpublikasikan.